Pemakaian Bahasa Batak Toba di Lingkungan Pendidikan - Simatupang , Ruth Remilani; Rohmadi , Muhammad; Saddhono , Kundharu (Jurnal Pendidikan Islam Indonesia, 2018)
The used of code-switching in learning Indonesian was an overview of the situation of how the interaction between students and teacher in learning. Code-switching used in regards to communicating certainly have functions. This study aimed to describe function code switching used by speakers at SMK of Marisi Medan. This research was a descriptive qualitative research. The subjects of study were the teacher and students. The objects were utterances of code-switching in Indonesian language learning at Vacational High School of Marisi Medan. Validity data technique used triangulation of data source and informant review. Data collection used listen and speak methods. Data analysis using the intralingual method. The result of research showed that function of code-switching at the time of process of Indonesian language learning are explained, reminded, reprimanded, emphasized, and asked.